Carnival as Contentious Performance - Lionel Arnaud (Journal of Festive Studies)
In the 1970s, in a context of increased racial tensions and growing nationalist claims, the use of rhythms, instruments, and clothing associated with Africa among the black populations of England, Guadeloupe, and Martinique became part of a cultural and political repertoire aimed at resurrecting and denouncing a long history of subordination. Similarly, the mobilization of carnival by Afro-Caribbean activists today can be considered as a tactical choice—that is to say, carnival has become part of the standardized, limited, context-dependent repertoires from which claim-making performances are drawn.